Evaluation of the Company's Financial Performance Using Economic Value Added (EVA) and Market Value Added (MVA) Methods - Susena, Karona Cahya (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Measurement of the company's financial performance is needed to determine success in achieving goals. The performance of a company can be seen from various aspects, one of which is from the financial aspect. Economic Value Added (EVA) and Market Value Added (MVA) are an approach method to assess a company's financial performance as an indicator of the creation of economic added value from an investment. The research method used in this paper is a quantitative descriptive analysis technique. The results of the study show that based on the Economic Value Added (EVA) method in 2018, 2019 and 2020 are considered very good. This can be seen from the positive EVA value where (EVA > 0), which means PT. Electronic City Indonesia Tbk succeeded in obtaining economic added value for three periods. Meanwhile, based on the results of calculations using the MVA (Market Value Added) method, the MVA data in 2018 produced was negative where the MVA value < 0. For 2019- 2020, although the MVA value achieved by the company decreased by 32%, the results still show the value which is positive where MVA > 0. To maintain a positive MVA the company needs to implement strategies and innovations to maintain business advantages that increase the value of the company so that the prosperity of shareholders can be maximized.